IMPLEMENTASI PENERIMAAN PAJAK PENGHASILAN (PPh) FISKAL USAHA MIKRO KECIL DAN MENENGAH DALAM PERATURAN PEMERINTAH NO. 46 TAHUN 2013 DI DESA PASAR PANGURURAN KECAMATAN PANGURURAN KABUPATEN SAMOSIR - Nina Andriany Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This study aims to determine the Implementation of Fiscal Income Tax (PPh) for Micro and Small and Medium Enterprises in Government Regulation No. 46 of 2013 in Pasar Pangururan Village, Pangururan District, Samosir Regency, as well as raising the level of tax awareness, especially SMEs for the development of Indonesia's economy, especially in Pasar Pangunguran Village, Pangunguran District, Samosir Regency. This study uses a quantitative data approach with multiple regression analysis models. The results showed that the Independent Variable, namely Fiscal Income Tax (PPh) Income, Micro, Small and Medium Enterprises, partially had a significant effect on Dependent Variables, namely Government Regulation No. 46 of 2013. Furthermore, simultaneously the Independent Variables namely Tax Revenue, Micro, Small and Medium Enterprises significantly influence the Dependent Variable, namely Government Regulation No. 46 of 2013. The implementation of Final Income Tax (PPh) Final for Small and Medium Enterprises has a significant positive effect on Government Regulation No. 46 of 2013 in Pasar Desa Pangunguran, Pangunguran District, Samosir Regency, both partially and simultaneously. The population in this study is Micro, Small and Medium Enterprises (MSMEs) in the Market Village of Pangunguran, Pangunguran District, Samosir District, the period of observation from 2013 to 2017, namely Final Income Tax (PPh). The sampling technique is based on purposive sampling in order to obtain a representative sample. The results of this study will be published in the scientific through the Scientific Abdi Sciences journal and the Journal of Accounting and Business that has ISSN, as well as holding a seminar on research results. In addition, the making of books for additional teaching material for Public Sector Accounting, Financial Management and Taxation courses.